(untitled) (Journal of Environmental Bioremediation and Toxicology, 2023)
Zn is a heavy metal often found at elevated concentrations in effluents as high as 300 ppm from the rubber processing industry as it is used for the vulcanization of rubber. The rice milling process produces rice husk as a by-product. It is one of the most important agricultural leftovers in terms of volume. The data of the sorption isotherm of Zn (II) (CV) sorption onto rice husk ash, which was plotted using linearized plots of isothermal models were reanalyzed using isothermal models using nonlinear regression. As the datapoints were small, isotherms with parameters of only up to three were utilized to prevent overfitting. The nineteen models were Henry, Langmuir, Freundlich, Temkin, Dubinin-Radushkevich, Jovanovic, Redlich-Peterson, Sips, Toth, Hill, Khan, BET, Vieth-Sladek, Radke-Prausnitz, Brouers–Sotolongo, Fritz-Schlunder III, Unilan, Fowler-Guggenheim and Moreau. Statistical analysis based on error function analyses such as root-mean-square error (RMSE), adjusted coefficient of determination (adjR2), accuracy factor (AF), bias factor (BF), Bayesian Information Criterion (BIC), corrected AICc (Akaike Information Criterion), and Hannan-Quinn Criterion (HQC) showed that Freundlich, followed by Langmuir and the Jovanovic models as the best top three models. The value of the maximum monolayer adsorption capacity for Zn binding to rice husk ash according to the Langmuir’s parameter qmL was 7.33 mg g-1 (95% Confidence interval from5.464 to 9.187), while bL (L mg-1), the Langmuir model constants was 0.011 L mg-1 (95% C.I. from 0.030 to 0.182). As the Freundlich equation is unable to model the maximum adsorption, the Halsey rearrangement of the Freundlich equation was utilized and gave the estimated maximum absorption of 7.20 mg g-1, which is very close to the experimental value. The constant values obtained in this study, especially the Langmuir model are largely different from the previously reported linearized approach.